Venezuela's Bolivarian Democracy : Participation, Politics, and Culture under Chávez. - Smilde, David (Duke University Press, 2011)
Looking beyond Hugo Chávez and the national government, contributors examine forms of democracy involving ordinary Venezuelans: in communal councils, cultural activities, blogs, community media, and other forums.